2021
DOI: 10.2991/assehr.k.210202.107
|View full text |Cite
|
Sign up to set email alerts
|

Problem Based Learning Teaching Approached in Nutrition Counselling Topic of Nutrition Education Subject by e-learn Computer Assisted Instruction of Undergraduate Nutrition Students at Publich Health Faculty of Andalas University

Abstract: Nutrition Conselling is one of topic of Nutrition Education Subject in third semester undergraduate nutrition students at Faculty of Public Health Univerisity of Andalas. During the learning process, teacher adopted Problem Based Learning approached by e-learn method in teaching and should use interactive mulimedia for student, not only hear, see and memorize concepts that are abstact. Student are expected to do is not just to remember the fact sothat students have no trouble during the learning process. Teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Also, Simarmata, et al (2018) reported that use of CAI for tutorials improves students' interest in learning computer networks fundamentals. An evaluation of e-learning by computer-based problem solving for nutrition education students by Symond, et al (2021) discovered that CAI is a useful method. A case study to assess students' ability by Suratno and Tonra (2018) discovered that CAI encourages students to be responsible for their learning.…”
Section: Fig 3 -Instrument For Data Collectionmentioning
confidence: 99%
“…Also, Simarmata, et al (2018) reported that use of CAI for tutorials improves students' interest in learning computer networks fundamentals. An evaluation of e-learning by computer-based problem solving for nutrition education students by Symond, et al (2021) discovered that CAI is a useful method. A case study to assess students' ability by Suratno and Tonra (2018) discovered that CAI encourages students to be responsible for their learning.…”
Section: Fig 3 -Instrument For Data Collectionmentioning
confidence: 99%